Sterculia diversifolia bears anti-cancer and immunomodulatory activities (Bangladesh Journal of Pharmacology, 2017)
The present study was aimed to evaluate the methanolic extract and subsequent solvents soluble fractions of Sterculia diversifolia bark for cytotoxic, anti-cancer and immunomodulatory activities. Phytochemical investigation confirmed the presence of alkaloids, flavonoids, saponins, glycosides, etc. In the cytotoxic activity, n-hexane showed potent activity (LD50: 7.0 µg/mL) followed by dichloromethane fraction (LD50: 16.2 µg/mL). In the anti-cancer activity, dichloromethane fraction showed potent activity (IC50: 5.9 µg/mL) followed by ethyl acetate fraction (IC50: 9.5 µg/mL). While in the immunomodulatory assay, ethyl acetate fraction showed a very significant activity (IC50: 21.0 µg/mL) followed by dicloromethane and n-butanol fractions (IC50: 25.0 and 25.3 µg/mL respectively). Hence, it is clear that S. diversifolia has anti-cancer and immunomodulatory agents.Video Clip of Methodology:ROS Assay: 2 min 9 sec   Full Screen   Alternate